2014
DOI: 10.1088/1612-2011/11/9/095601
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity red and infrared lasers on XPA and XPC gene expression

Abstract: Laser devices emit monochromatic, coherent, and highly collimated intense beams of light that are useful for a number of biomedical applications. However, for low-intensity lasers, possible adverse effects of laser light on DNA are still controversial. In this work, the expression of XPA and XPC genes in skin and muscle tissue exposed to low-intensity red and infrared lasers was evaluated. Skin and muscle tissue of Wistar rats were exposed to low-intensity red and infrared lasers at different fluences in conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Our results also emphasizing that mRNA expression from genes related to DNA repair systems can be differentially induced in skin and muscle tissues after exposure to lowintensity lasers [43]. There are few studies comparing laser effects on mRNA expression from genes related to DNA lesion repair in different tissues.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our results also emphasizing that mRNA expression from genes related to DNA repair systems can be differentially induced in skin and muscle tissues after exposure to lowintensity lasers [43]. There are few studies comparing laser effects on mRNA expression from genes related to DNA lesion repair in different tissues.…”
Section: Discussionsupporting
confidence: 50%
“…Previous data demonstrated that infrared laser exposure differently affects mRNA expression from genes coding enzymes involved in BER pathway of nuclear (APE1, OGG1, APEX1, and APEX2) [19,20,39] and mitochondrial (γ-polimerase) [20] DNA repair in skin and muscle tissue after infrared laser exposure. XPA and XPC mRNA expression is also differently altered in skin and muscle tissue after low-intensity infrared laser [43]. These findings could be explained due to different chromophores or different chromophore concentrations in skin and muscle cells.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, no telomere shortening was observed in healthy animals irradiated with a laser at 20 J cm −2 . A study on the evaluation of the influence of a low-power laser therapy on parameters of oxidative stress and DNA damage in skeletal muscle and plasma of rats with heart failure demonstrated that the DNA damage index had a significant increase at 21 J cm −2 compared to that at 3 J cm −2 , which suggests that high doses of a low-power laser seem to increase the DNA damage [ 41 ]. On the other hand, a study on the evaluation of DNA damage in blood cells of healthy animals after red and infrared laser irradiations demonstrated that the DNA damage is not dependent on the fluence because the irradiation at 50 J cm −2 induced higher levels of DNA damage in blood cells than those at 25 and 100 J cm −2 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although, biological effects caused by free radicals induced by low-level laser radiation are controversial, the possible adverse effects on cells and DNA damage after laser exposure have been reported in eukaryotic cells [13] and prokaryotic cells, at different powers, wavelengths, and fluences [12,14], as well as inducing adaptation or DNA damage at sub-lethal levels [14]. In addition, low-level lasers alter the relative expression of mRNA from DNA repair genes in tissues from Wistar rats [13,[15][16][17].…”
Section: Laser Physicsmentioning
confidence: 99%